COMPARISON OF ULTRASOUND AND ISCHAEMIC COMPRESSION ON LATENT TRIGGER POINT IN UPPER TRAPEZIUS. - DR. PREETI GAZBARE,; DR. TUSHAR PALEKAR,; DR.MANISHA RATHI, (International Journal of Pharma and Bio Sciences, 2014)
Myofascial trigger point (TrP) is hyperirritable area located in a taut band of skeletal muscle that is painful on compression, gives characteristic referred pain & an autonomic response to a remote area. Trapezius acts continuously to hold the head upright, leading to formation of TrP.To compare effect of ultrasound (US) & ischaemic compression(IC) on latent TrP in upper trapezius. Pretest-posttest experimental group design. 30 subjects were randomly assigned from inclusion criteria in 2 groups, group A (n=15) treated with US & B (n=15) with IC, for 7 days. Outcome measure was feel threshold (TF), pain threshold (TP), pain tolerance threshold (PTT) by using galvanic current. paired and unpaired t test was applied. Both the groups showed improvement (p<0.00). Both US & IC are equally effective in treating TrP showing increase in TF,TP,TT and subsequently reduction in pain sensitivity on TrP.